A Competência em informação para a construção de conhecimento no processo decisório: estudo de caso na Duratex de Agudos (SP) - Yafushi, Cristiana Aparecida Portero [UNESP] (2015)
Organizations experience a dynamic environment that brings many technological innovations. The information tools and the Internet provide fast access to information sources and flows, enabling the communication technology to disseminate information quickly. However, the society that aims to conquer information also needs competent professionals in information (CoInfo), who manage information and organizational resources and know how to access and use the information effectively, building knowledge both individually and collective, which is applicable in their decision - making processes and generate competitive advantages for decision- making. Information literacy is a higher value strategic resource for the organization to create new knowledge that can be disseminate, shared and integrate actions which will lead to the acquisition of appropriate, reliable and assertive decisions a new level in the competitive environment. The requirements of the research problems are: to identify how managers access, seek and use information in their decision - making processes and outline the skills to perform their successful management the objective is to analyze the Information Literacy of managers and their application to decision - making at Duratex SA, a company located in Agudos/SP to stimulate competitive advantage in the business market. Therefore, the bibliographical research is important to structure the theory and understanding, which was essential to develop a case study, characterized as exploratory, descriptive and qualitative. Data collection occurred through: a) documentary research, according to information available on the organization's website and e-mail exchanges with the participants, b) questionnaire technique c) structured interview. The documental research enabled the characterization of - Duratex SA / and the target population. The analysis of data collection is based on 'content analysis' developed by Laurence Bardin. It also...